Bio‐adhesive Nanoporous Module: Toward Autonomous Gating. Issue 16 (3rd March 2021) - Jo, Hyuna; Kitao, Takashi; Kimura, Ayumi; Itoh, Yoshimitsu; Aida, Takuzo; Okuro, Kou
Abstract: Here we report a bio‐adhesive porous organic module ( Glue COF) composed of hexagonally packed 1D nanopores based on a covalent organic framework. The nanopores are densely decorated with guanidinium ion (Gu + ) pendants capable of forming salt bridges with oxyanionic species. Glue COF strongly adheres to biopolymers through multivalent salt‐bridging interactions with their ubiquitous oxyanionic species. By taking advantage of its strong bio‐adhesive nature, we succeeded in creating a gate that possibly opens the nanopores through a selective interaction with a reporter chemical and releases guest molecules. We chose calmodulin (CaM) as a gating component that can stably entrap a loaded guest, sulforhodamine B (SRB), within the nanopores ( CaM COF⊃SRB). CaM is known to change its conformation on binding with Ca 2+ ions. We confirmed that mixing CaM COF⊃SRB with Ca 2+ resulted in the release of SRB from the nanopores, whereas the use of weakly binding Mg 2+ ions resulted in a much slower release of SRB. Abstract : A porous covalent organic framework ( Glue COF) carrying guanidinium ion pendants has been developed that can accommodate guests and bind to biopolymers. The strong bio‐adhesive nature of Glue COF was used to noncovalently bind to calmodulin (CaM), which acted as a gating component for the guest‐loaded 1D nanopores ( CaM COF⊃guest). The conformational change of the CaM gate upon selective binding with Ca 2+ enabled the release of guest molecules.